PERSEPSI PENGOLAH DATA TERHADAP EFEKTIVITAS PDE HOTEL BERBINTANG DI KOTA DENPASAR - SUWARTHA, I KETUT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 2 (2010))
The development of information technology provides more expectations for the businessman, spesifically in the hotel sector. Nevertheless, in it’s implementation raise expectation gap between the user of the information and data processing in the Electronic Data Processing (PDE). The objective of this research is to find out the effectivity and dimension that should be improved on the side of data processing perception in the Electronic Data Processing (PDE) of  star hotels  in Denpasar. The data collected by using questionnaire and interview and the data analysis technique used in this research is quantitative analysis technique. The conclusions from the analysis are (1) data processing perception included in the category of very effective by 81.64%, (2) there are three dimensions which needs more attention and improved, namely time dimension, report variation dimension or out put, information quality dimension.
Keywords: information technology, information gap, effectivity, data processing